Human papillomavirus infection does not predict response to interferon therapy in ocular surface squamous neoplasia - Galor, Anat (Ophthalmology, 2015)
PURPOSE: To identify the frequency of human papilloma virus (HPV) in ocular surface squamous neoplasia (OSSN), and evaluate differences in clinical features and treatment response of HPV positive versus negative tumors. DESIGN: Retrospective case series. PARTICIPANTS: 27 patients with OSSN METHODS: OSSN specimens were analyzed for the presence of HPV. Clinical features and response to interferon were retrospectively determined and linked to the presence (versus absence) of HPV. MAIN OUTCOME MEASURES: Clinical characteristics of OSSN by HPV status. RESULTS: Twenty one of 27 tumors (78%) were HPV positive. HPV genotypes identified included HPV 16 in 10 (48%), HPV 31 in 5, HPV 33 in 1, HPV 35 in 2, HPV 51 in 2, and a novel HPV in 3 (total 23 as one tumor had 3 genotypes identified). Tumors found in the superior limbus were more likely to be HPV positive (48% vs 0%, Fisher exact P = 0.06). HPV 16 positive tumors were larger (68mm(2) vs 34 mm(2), Mann Whitney U P = 0.08) and were more likely to have a papillomatous morphology (50% vs 12%, Fisher exact P = 0.07) compared to HPV 16 negative tumors. HPV status was not found to associate with response to interferon therapy (Fisher exact P = 1.0). Metrics found to associate with a non-favorable response to interferon were male gender and tumors located in the superior conjunctivae. CONCLUSIONS: HPV presence in OSSN appears more common in lesions located in the non-exposed, superior limbus. HPV presence does not seem to be required for a favorable response to interferon therapy.